BEHAVIORAL FINANCE: THE IMPACT OF HERDING BEHAVIOR ON INVESTMENT DECISIONS: The Case Of Companies Listed In The Lq-45 Index In The Indonesian Stock Exchange (BEI) For The Period 2018-2020 - Khalingga, Muhammad Ariq; Galih, Wening; Risnanto, Slamet; Abimanyu, Ketut (Multifinance, 2024)
The purpose of this study is to describe and analyze the effect of herding behavior on investment decisions in companies included in the LQ-45 index of the Indonesia Stock Exchange (IDX) for the period 2018-2022 Research method will use descriptive verification method. To test the hypothesis to determine the influence or causal relationship of the hypothesis that has been proposed. In this study, the verification method is used to determine how much influence herding behavior has on investment decisions.  Findings show the results of hypothesis testing that, the independent variable herding behavior has a positive and significant effect on investment decisions, which means that with the panic of investors over the unclear sources of information and market conditions that will affect portfolio performance or can be said to be informational cascades conditions cause the loss of objectivity of an investor and lead to an irrational attitude so that investment decisions are made by following signals and information owned by other investors who are considered high skilled to be used as a reference for portfolio performance.  Value, according to the test results that have been carried out, the herding behavior variable results in a coefficient value of 1.61 with a significance level of 0.0198 <0.05, and the test results for the Coefficient of Determination in this study, show an RSquare value of 0.081119, meaning that 8.1% of the dependent variable Investment Decision can be explained by the independent variable, namely Herding Behavior. For 91.9% can be explained by other factors outside of Herding Behavior.